1996
DOI: 10.3109/02713689609000766
|View full text |Cite
|
Sign up to set email alerts
|

An intravitreal device providing sustained release of cyclosporine and dexamethasone

Abstract: We conclude that the device maintains potentially therapeutic levels of both cyclosporine and dexamethasone in the vitreous. Reversible electroretinographic abnormalities are attributable to cyclosporine. A sustained-release device containing cyclosporine and dexamethasone may be useful for reducing inflammation in diseases such as proliferative vitreoretinopathy and uveitis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(22 citation statements)
references
References 40 publications
0
21
0
1
Order By: Relevance
“…The toxicity of formulation 3 possibly resulted from CsA itself, judging from the comparison of formulation 3 (CsA-PLGA-MS with PF68) with PLGA-MS with or without PF68, and this is consistent with the previous reports about the CsA device. 13 The same test also demonstrated that no retinal toxicity of PF68 was observed. Additionally, PF68 was approved by the U.S. Food and Drug Administration for use in humans, even for intravenous injection.…”
Section: Therapeutic Evaluation Of Csa-ms On Uveitismentioning
confidence: 78%
“…The toxicity of formulation 3 possibly resulted from CsA itself, judging from the comparison of formulation 3 (CsA-PLGA-MS with PF68) with PLGA-MS with or without PF68, and this is consistent with the previous reports about the CsA device. 13 The same test also demonstrated that no retinal toxicity of PF68 was observed. Additionally, PF68 was approved by the U.S. Food and Drug Administration for use in humans, even for intravenous injection.…”
Section: Therapeutic Evaluation Of Csa-ms On Uveitismentioning
confidence: 78%
“…Proposed treatments should guarantee efficient levels of therapeutic agents at the right target during this time. There are a few older reports that propose sustained delivery systems for treating PVR (Enyedi et al, 1996;Yang et al, 1998;Zhou et al, 1998). Currently we have gained more clinical experience with drug delivery systems, and there are new possibilities that should be explored.…”
Section: A Look Into the Futurementioning
confidence: 97%
“…24,36 To overcome the limitations of delivering drugs to the eye by topical administration, systemic injection, and intravitreal injection, interest has increased in the use of sustained release delivery methods. 2,6,11,31,42 Well known is the intravitreal ganciclovir implant (Vitrasert, Bausch & Lomb) for treating cytomegalovirus retinitis in AIDS. 9 The distribution of injected materials in the vitreous has been studied theoretically and experimentally 13,34,41 and the movement of drugs released from an implant in the vitreous has been studied theoretically.…”
Section: Introductionmentioning
confidence: 99%